Considerations Regarding the Use of Artificial Intelligence in Financial Management and Accounting in State Pre-University Educational Institutions - Panait (Ion), Mihaela; Musat (Ciobota), Lidia; Cosor (Peneoasu), Margareta (Acta Universitatis Danubius. Œconomica, 2025)
In an era where technology is becoming increasingly omnipresent and essential for decision-making and management processes, public pre-university educational institutions face complex challenges in resource management, performance monitoring, and risk management. In this context, the interest in utilizing Artificial Intelligence (AI) technologies to enhance financial management and accounting in these institutions has surged in recent years. This interest is fueled by the rapid advancement of AI technology and the growing need for innovative solutions to address these challenges. AI offers remarkable possibilities for automating processes, analyzing data, and making decisions, facilitating a more efficient and dynamic approach to resource and risk management in these institutions. This study begins with a detailed analysis of the current context and specific needs within the educational sector, contributing by proposing advanced technological solutions and identifying practical recommendations aimed at improving financial management and refining accounting practices in pre-university educational institutions.